2008
DOI: 10.1007/s00330-008-1029-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of inflammatory breast carcinoma and acute mastitis. A comparative study

Abstract: The aim of this study was to evaluate the potential of magnetic resonance mammography (MRM) to distinguish inflammatory breast carcinomas (IBC) from acute mastitis (AM). This study compared MRM examinations of two selected groups of patients: 48 subjects with IBC and 42 patients with AM. No statistical differences were revealed between the two groups for morphology of masses and of non-mass-like enhancement, breast enlargement, diffuse skin thickening, abnormal nipple configuration, prominent vessels, and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 34 publications
8
50
2
4
Order By: Relevance
“…MRI findings of IGM are T2 hyperintensity, major contrast enhancement at subaerolar region, moderate or slow enhancement in an early phase and increased enhancement pattern or plato pattern in the late phase of contrast injection, absence of perifocal, prepectoral or pectoralis muscle edema and absence of findings suggesting pectoralis muscle invasion (nonvisualization of prepectoral fat planes or pathologic contrast enhancement of pectoralis muscle). These MRI findings together with an absence of mass on US and MG support the IGM [20][21]. In our study, MRI findings were similar to literature.…”
Section: (80)supporting
confidence: 91%
“…MRI findings of IGM are T2 hyperintensity, major contrast enhancement at subaerolar region, moderate or slow enhancement in an early phase and increased enhancement pattern or plato pattern in the late phase of contrast injection, absence of perifocal, prepectoral or pectoralis muscle edema and absence of findings suggesting pectoralis muscle invasion (nonvisualization of prepectoral fat planes or pathologic contrast enhancement of pectoralis muscle). These MRI findings together with an absence of mass on US and MG support the IGM [20][21]. In our study, MRI findings were similar to literature.…”
Section: (80)supporting
confidence: 91%
“…The most typical finding in IBC is skin involvement with diffuse changes, which previous authors have reported in 75% of cases [14,21]. Even in our series, the main typical feature of IBC was skin thickening which, together with oedema, was present in over 87% of cases.…”
Section: Discussioncontrasting
confidence: 55%
“…In letteratura, alcuni lavori si sono occupati dei rilievi semeiotici del IBC [12][13][14][15][16][17][18][19][20], pochi di questi hanno trattato gli aspetti di imaging RM [12][13][14][15] e solo un recente lavoro analizza le manifestazioni RM del IBC e la diagnosi differenziale con il LABC [21]. Lo scopo di questo studio è quindi verificare l'esistenza di rilievi RM specifici di carcinoma infiammatorio e dimostrarne l'accuratezza statistica nella diagnosi differenziale tra carcinoma infiammatorio e tumore localmente avanzato della mammella.…”
Section: Patientsunclassified
See 1 more Smart Citation
“…Three postinitial curve types were defined [26][27][28]: (1) continuous increase (increase [10%); (2) plateau phenomenon (deviation of the signal curve between ?10% and -10%); (3) wash-out sign (decrease [10%). For the analysis of the MRI morphology, the Breast Imaging Reporting and Data System (BI-RADS) atlas [29] and further morphologic characteristics, in detail described in the literature [27,30,31], were used.…”
Section: Image Interpretationmentioning
confidence: 99%